Updated basic glossary of periodontal and orthodontic dental terms, English-Spanish - Betancourt García, Ana Ibis (2023)
The large volumes of scientific information generated daily require health professionals to be constantly updated. Most of this information comes from English-speaking countries or is published in that language; hence, the professional must learn that language to be able to appropriate and/or disseminate as much as possible all this scientific creation. In this context, glossaries of terms from different languages contribute to cover this need. This glossary is conceived as a quick and up-to-date search tool for English terms related to orthodontics and periodontics. It compiles more than 150 terms from these specialties and is intended for students and professionals who wish to consult the meaning of words specific to these fields efficiently. It is not intended to present all the words and phrases pertaining to these specialties, as that would be impossible. It should be clarified that terms with spelling similar to Spanish were excluded, except those whose meaning is not the same.